The impact of noise on detecting the arrival angle using the root-WSF algorithm - Btissam Boustani; Abdennaceur Baghdad; Aicha Sahel; Abdelhakim Ballouk; Abdelmajid Badri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This article discusses three standards of Wi-Fi: traditional, current and next-generation Wi-Fi. These standards have been tested for their ability to detect the arrival angle of a noisy system. In this study, we chose to work with an intelligent system whose noise becomes more and more important to detect the desired angle of arrival. However, the use of the weighted subspace fitting (WSF) algorithm was able to detect all angles even for the 5th generation Wi-Fi without any problem, and therefore proved its robustness against noise.